Heart Rate Variability and Cognitive Function In Middle-Age Adults: The Coronary Artery Risk Development in Young Adults. (25th July 2017) - Zeki Al Hazzouri, Adina; Elfassy, Tali; Carnethon, Mercedes R; Lloyd-Jones, Donald M; Yaffe, Kristine
Abstract: BACKGROUND: Low heart rate variability (HRV), a marker of cardiac autonomic dysfunction, has been associated with major risk factors of cognitive impairment. Yet, the direct association of HRV with cognitive function remains relatively unexplored, particularly in midlife. METHODS: In 2005, 2 measures of short-term HRV, the SD of normal-to-normal intervals (SDNN) and the root mean square of successive differences (RMSSD), were calculated for participants of the Coronary Artery Risk Development in Young Adults study, and then categorized into quartiles. Five years later, 3 cognitive tests were administered for verbal memory ("Rey Auditory-Verbal Learning Test", RAVLT, range 0–15), processing speed ("Digit Symbol Substitution Test", DSST, range 0–133), and executive function ("Stroop interference"). RESULTS: Two thousand one hundred and eighteen participants (57.7% female, 42.2% Black) with a mean baseline age of 45.3 years were included in this analysis. In demographic-adjusted models, compared to participants with quartile 1 SDNN (lowest quartile), participants in the upper quartiles of SDNN scored better on the DSST (quartile 4: β = 1.83 points better, P = 0.03; and quartile 3: β = 1.95 points better, P = 0.03) and on the stroop (quartile 3: β = 1.19 points better, P < 0.05; and quartile2: β = 1.44 points better, P = 0.02). After adjusting for behavioral and cardiovascular risk factors, higher quartile SDNN remained significantly associated with better stroop score (quartile 3: β = 1.21 points better, P = 0.04; and quartile 2: β = 1.72 points better, P < 0.01) but not with DSST. There was no association between quartile of RMSSD and cognitive function, from fully adjusted models. CONCLUSIONS: Our findings suggest that higher quartile SDDN is associated with better executive function in midlife, above, and beyond cardiovascular risk factors.